2014
DOI: 10.1242/bio.20149811
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose non-fermenting related kinase enzyme is essential for cardiac metabolism

Abstract: In this study, we have identified a novel member of the AMPK family, namely Sucrose non-fermenting related kinase (Snrk), that is responsible for maintaining cardiac metabolism in mammals. SNRK is expressed in the heart, and brain, and in cell types such as endothelial cells, smooth muscle cells and cardiomyocytes (CMs). Snrk knockout (KO) mice display enlarged hearts, and die at postnatal day 0. Microarray analysis of embryonic day 17.5 Snrk hearts, and blood profile of neonates display defect in lipid metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Sections were blocked for non-specific binding in 1.5% normal goat serum and incubated with the primary SNRK antibody (1:100; Abcam, ab96762) overnight at 4°C. The specificity of this antibody for SNRK has been previously validated by our lab(8). For negative controls, a section from each sample was incubated in PBS without primary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were blocked for non-specific binding in 1.5% normal goat serum and incubated with the primary SNRK antibody (1:100; Abcam, ab96762) overnight at 4°C. The specificity of this antibody for SNRK has been previously validated by our lab(8). For negative controls, a section from each sample was incubated in PBS without primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Studies show it is involved in neuronal apoptosis(6), blood vessel development(7), and cardiac development, metabolism and function in mammals(8). SNRK is also reported to directly phosphorylate the mTOR binding partner raptor which results in inhibition of mTOR complex 1 (mTORC1) and causes cell cycle arrest(9).…”
Section: Introductionmentioning
confidence: 99%
“…Methodologies related to protein estimation, quantitation were described previously 7 . The following antibodies were used: anti- myosin-binding subunit (MBS; BioLegend), anti-phospho MBS (pMBS; Cell Signaling Technology/MBL International); anti-ROCK1 (BD Bioscience); anti-ROCK2 (BD Bioscience); anti-extracellular signal-regulated kinase (ERK; Cell Signaling Technology); anti-phospho ERK (pERK; Cell Signaling Technology); anti-protein kinase B (AKT; Cell Signaling Technology); anti-phospho AKT (pAKT; Cell Signaling Technology); anti-inhibitor of kappa B kinase (IKK; Cell Signaling Technology); anti-phospho IKK(pIKK; Cell Signaling Technology); anti-Tubulin (Sigma), anti-rabbit horseradish peroxidase (HRP; Cell Signaling Technology) and anti-mouse HRP (Cell Signaling Technology).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work 7 , we reported that the global Snrk KO mice die within 24 hours after birth, displayed enlarged hearts, and lethality is associated with metabolic defects in cardiac tissues. SNRK maintains metabolic homeostasis via regulation of the phosphorylated acetyl-coA carboxylase (pACC)-phosphorylated AMPK (pAMPK) pathway during this transitional period in development 7 . Furthermore, cardiac specific conditional Snrk KO ( Snrk cmcKO) adult mice display severe cardiac functional deficits and lethality within 8–10 months.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation